2006
DOI: 10.1121/1.4781605
|View full text |Cite
|
Sign up to set email alerts
|

Tongue dorsum location and tongue root retraction in alveolar and palatal clicks in the endangered language N/uu

Abstract: Traill (1985) describes Xoo clicks as having velar posterior constriction locations (PCL). Miller et al. (to appear) show that the PCLs of Khoekhoe alveolar and palatal clicks are uvular and uvulo-pharyngeal. Ladefoged and Maddieson (1996) discuss clicks involving a uvular posterior release location (PRL) (and an implied velar PCL). An ultrasound investigation of velar and uvular pulmonic stops, alveolar and palatal velar clicks, and palatal uvular clicks, in the endangered language N/uu is presented. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…At least since Doke (1923), the phonetic literature has assumed that all basic click types are produced with a velar posterior place of articulation. Miller, Namaseb & Iskarous (2007) have, however, shown that the palatal and postalveolar clicks in Khoekhoe in fact have different posterior places of articulation, and we will see that the same is true in N|uu (Miller et al 2006). Our first goal here is to provide evidence supporting our claim that the posterior constrictions in N|uu alveolar [!]…”
Section: Posterior Constrictions Across Click Typesmentioning
confidence: 52%
See 1 more Smart Citation
“…At least since Doke (1923), the phonetic literature has assumed that all basic click types are produced with a velar posterior place of articulation. Miller, Namaseb & Iskarous (2007) have, however, shown that the palatal and postalveolar clicks in Khoekhoe in fact have different posterior places of articulation, and we will see that the same is true in N|uu (Miller et al 2006). Our first goal here is to provide evidence supporting our claim that the posterior constrictions in N|uu alveolar [!]…”
Section: Posterior Constrictions Across Click Typesmentioning
confidence: 52%
“…This runs contrary to descriptions dating back at least to Doke (1923). Like Miller, Namaseb & Iskarous (2007) and Miller et al (2006), we use ultrasound data to show that the central alveolar [!] and palatal [ ] clicks differ in the position of the tongue root and that both have post-velar places of articulation.…”
Section: Airstream Contoursmentioning
confidence: 70%
“…Like any other click, [ʞ] is produced with an ingressive velaric (or lingual, cf. Miller et al 2006, Miller et al 2007) airstream. The oral cavity is closed in two places: at the back and at the front of the mouth.…”
Section: Back-released Velar Click [ʞ]mentioning
confidence: 99%